The natural history of injecting drug use in a Dublin community (1985-1995) - O'Kelly, Fergus Desmond (Trinity College (Dublin, Ireland). Department of Public Health and Primary Care, 2000)
The number of drug users within Ireland and the European Union is increasing. It is estimated that there are about 14 thousand drug users in Ireland and a total of between 1.5 and 2 million within the European Union. Drug related AIDS cases account for 50% of all AIDS cases in Europe. The high prevalence of HIV inlection in the drug using population and the increasing numbers using illicit drugs has posed many medical and psychosocial problems not only for individuals, but also for their families and communities especially so over the last two decades.
Keywords: Community Health and General Practice, M.D.; M.D. Trinity College Dublin